Presentation of clinical-diagnostic and epidemiological activity of the Occupational Health, Hygiene, Toxicology and Prevention Unit of the ASST Spedali Civili of Brescia - De Palma, Giuseppe; Madeo, Egidio; Monzio Compagnoni, Marina; Fostinelli, Jacopo; Apostoli, Pietro (La Medicina del Lavoro, 2018)
The paper describes the clinical–diagnostic and epidemiologic activities that are performed within the Occupational Health Unit at the University Hospital (ASST, Azienda Socio-Sanitaria Territoriale, Socio-Sanitary Territorial Enterprise) Spedali Civili of Brescia. The Unit works in the context of the Lombard UOOML (Unità Operative di Medicina del Lavoro, Occupational Health Units) network, prominently in the field of industrial hygiene and toxicology. Qualified diagnoses of work-related diseases are pursued after full characterization on one side of the actual exposure context and related occupational risks and on the other side of the clinical-pathological features of diseases. The epidemiological branch operates in the context of the Regional programs of active research of work-related diseases, including work-related cancer.